Irreplaceable: Exploring identity and relationships through the discussion of invaluable personal objects. Issue 2 (3rd April 2017) - Scharp, Kristina M.; Canfield, Clair
Abstract : Courses: Interpersonal Communication, Family Communication, Relational Communication. Objectives: Students reflect on and discuss how personal objects are connected to their identity and relationships with others. This activity illustrates the ways course concepts such as relational metaphors, stories, rules, rituals, and other patterns of communication influence the meaning we ascribe to an object and how that object helps to construct beliefs about ourselves and important others. This exercise can also help students connect with each other in a supportive environment.